Bridging Gut Inflammation and Cognitive Decline: Exploring the Pathogenesis of Inflammatory Bowel Disease-associated Dementia (Asian Journal of Pharmaceutics (AJP), 2025)
Dementia, characterized by a progressive decline in cognitive functions such as memory, thinking, problem-solving,language, and behavior, is most commonly associated with Alzheimer’s disease, a prevalent neurodegenerativedisorder. Recent epidemiological evidence suggests a potential link between inflammatory bowel disease(IBD) and dementia, prompting investigations into this association. This abstract reviews current research onthe pathogenesis of IBD-associated dementia, focusing on animal model studies that mimic chronic intestinalinflammation similar to IBD. The pathogenesis of IBD is related to dysbiosis of the gut microenvironment, andvarious epidemiological studies show that patients with IBD are more likely to have dementia in future. Thus,targeting IBD as a potential therapeutic approach for dementia has garnered increasing attention. Furthermore,IBD-induced neuroinflammation affects brain function and contributes to dementia. In this review, we highlightthe role of microbiota and their metabolites in mediating the pathogenesis of IBD-associated dementia. Disruptionsin gut microbiota can lead to altered metabolite profiles that may influence neuroinflammatory pathways andexacerbate cognitive impairment. Furthermore, immune-mediated mechanisms play a critical role in this process.The microbiota-gut-brain axis, which links gut microbiota with brain function, has emerged as a significantpathway through which IBD-related changes in microbiota and metabolites contribute to dementia. Overall, theresearch underlines the complex interplay between chronic intestinal inflammation, microbiota alterations, andimmune responses in the development of dementia associated with IBD.